Preparation of pyrrolizinone derivatives via sequential transformations of cyclic allyl imides: synthesis of quinolactacide and marinamide. Issue 12 (7th March 2018) - Simic, Milena; Tasic, Gordana; Jovanovic, Predrag; Petkovic, Milos; Savic, Vladimir
Abstract : A facile synthetic route toward the preparation of pyrrolizinone derivatives has been developed and applied for the synthesis of quinolactacide/marinamide. Abstract : A facile synthetic route has been developed for the preparation of pyrrolizinone derivatives employing N -allyl imides as starting materials. The nucleophilic addition of a vinyl Grignard reagent/RCM/elimination sequence afforded pyrrolizinones in good yields and has been applied for the preparation of naturally occurring quinolactacide and marinamide.